A geographic information system for gas power plant location using analytical hierarchy process and fuzzy logic - F.S. Alavipoor; S. Karimi; J. Balist; A.H. Khakian (Global Journal of Environmental Science and Management)
This study recommends a GIS-based (Geographic Information Systems) and multi-criteria evaluation for site selection of gas power plant in Natanz City of Iran. The multi-criteria decision framework integrates legal requirements and physical constraints related to environmental and economic concerns. It also builds a hierarchy model for gas power plant suitability. The methodologies used for site selection include analytic hierarchy process (AHP), fuzzy set theory and weighted linear combination. The AHP (analytic hierarchy process) is a multi-criteria approach which is used to establish the relative importance of criteria. The AHP makes pair-wise comparisons of relative importance between hierarchy elements categorized by environmental decision criteria. In the next step, the fuzzy set theory is used to standardize criteria through different fuzzy membership functions and fuzzy layers are formed by using fuzzy operators in ArcGIS environment. Subsequently, they are categorized into 6 classes using Reclassify Function. Weighted linear combination is used to combine the criteria layers. Finally, the two approaches are analyzed in order to locate the most suitable site to establish a gas power plant. According to the results, using GAMMA fuzzy operator is considered suitable for this site selection.